2012
DOI: 10.5194/se-3-53-2012
|View full text |Cite
|
Sign up to set email alerts
|

Constraining fault interpretation through tomographic velocity gradients: application to northern Cascadia

Abstract: Abstract. Spatial gradients of tomographic velocities are seldom used in interpretation of subsurface fault structures. This study shows that spatial velocity gradients can be used effectively in identifying subsurface discontinuities in the horizontal and vertical directions. Three-dimensional velocity models constructed through tomographic inversion of active source and/or earthquake traveltime data are generally built from an initial 1-D velocity model that varies only with depth. Regularized tomographic in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Terminations of reflections on either side of the fault zone and northdipping reflections further north constrain the dip of the fault to be sub-vertical to north dipping at an angle greater than 30 degrees (Hayward et al, 2006). Ramachandran (2012) showed that spatial velocity gradients can be effectively used in identifying subsurface discontinuities in the horizontal and vertical directions. This interpretation resulted in inferring the Washington state location of the DMFZ much more clearly.…”
Section: Devil's Mountain Fault Zonementioning
confidence: 99%
“…Terminations of reflections on either side of the fault zone and northdipping reflections further north constrain the dip of the fault to be sub-vertical to north dipping at an angle greater than 30 degrees (Hayward et al, 2006). Ramachandran (2012) showed that spatial velocity gradients can be effectively used in identifying subsurface discontinuities in the horizontal and vertical directions. This interpretation resulted in inferring the Washington state location of the DMFZ much more clearly.…”
Section: Devil's Mountain Fault Zonementioning
confidence: 99%